2014
DOI: 10.4081/audiores.2014.110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compression, Digital Noise Reduction and Directionality on Envelope Difference Index, Log-Likelihood Ratio and Perceived Quality

Abstract: The aim of the present study was to evaluate the use of the envelope difference index (EDI) and log-likelihood ratio (LLR) to quantify the independent and interactive effects of wide dynamic range compression, digital noise reduction and directionality, and to carry out self-rated quality measures. A recorded sentence embedded in speech spectrum noise at +5 dB signal to noise ratio was presented to a four channel digital hearing aid and the output was recorded with different combinations of algorithms at 30, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…This could be because of the way that noise reduction strategies work -they increase the temporal envelope modulation depth in the process of cutting down noise [16], which results in higher EDI. However, these findings go against the results of the study by Geetha and Manjula [19]. The difference might be due to a difference in stimulus presentation: in the current study, the sources of speech and noise were spatially separate (meaning that, as the literature demonstrates, directionality could work more effectively [28]), whereas in the earlier study the speech and noise emanated from the same source.…”
Section: Effect Of Algorithms On Edi For Sentencescontrasting
confidence: 97%
See 2 more Smart Citations
“…This could be because of the way that noise reduction strategies work -they increase the temporal envelope modulation depth in the process of cutting down noise [16], which results in higher EDI. However, these findings go against the results of the study by Geetha and Manjula [19]. The difference might be due to a difference in stimulus presentation: in the current study, the sources of speech and noise were spatially separate (meaning that, as the literature demonstrates, directionality could work more effectively [28]), whereas in the earlier study the speech and noise emanated from the same source.…”
Section: Effect Of Algorithms On Edi For Sentencescontrasting
confidence: 97%
“…A study by Geetha and Manjula [19] has quantified the acoustic changes induced by compression, DNR, and directionality -in isolation and in combination -using EDI and measured the quality ratings. The authors recorded the output of the hearing aid in a 2 cc coupler and processed it to obtain an EDI.…”
Section: Envelope Difference Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study in 2019, the same authors used the same sentence lists to evaluate the correlation between temporal integration and temporal envelope perception in noise [36]. The sentences have also been used to study the effect of the number of talkers in background speech babble on acceptable noise levels [37] and the effect of compression, digital noise reduction, and directionality on envelope difference index, log-likelihood ratio, and perceived quality [38].…”
Section: Applicationsmentioning
confidence: 99%
“…The minimum NR gradation had the least effect on the noise, i.e., NR 'on' at minimum gradation was almost equivalent to NR 'off' position across all the types of noise. Geetha and Manjula [14] suggested that compression, DNR, and directionality are similar in terms of temporal changes that they introduce. Hence the results of EDI with manipulating the compression parameter may be utilized to compare with the EDI results while manipulating the NR algorithm.…”
Section: Bmentioning
confidence: 99%